THE INFLUENCE OF INTERNAL FACTORS, BANK SIZE AND GOOD CORPORATE GOVERNANCE ON THE PERFORMANCE OF COMMERCIAL BANK LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2021-2022 - Nurhana, Inka Ayu; Triyono, Triyono; Sasongko, Noer (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to test whether there is an influence between the NPL ratio, OER, CAR, LDR, SIZE and GCG on the performance of commercial banks on the BEI in 2021-2022. The population in this research are management parties involved in commercial banking companies listed on the IDX. The number of samples in this research was 36 companies in 2021-2022. The sampling technique uses a purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS version 25. The results of this research show that the variables NPL, OER, LDR, LnSIZE do not have a significant effect on Commercial Bank Performance (ROA), while CAR and GCG has a significant effect on Commercial Bank Performance (ROA ). Simultaneously the variables NPL, OER, CAR, LDR, Company Size, and GCG, have an influence on Commercial Bank Performance (ROA)